2014
DOI: 10.1186/1477-5751-13-6
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Saccharomyces boulardii does not prevent the experimental mucositis in Swiss mice

Abstract: BackgroundThe antimetabolite chemotherapy 5-Fluorouracil is one of the most commonly prescribed drugs in clinical cancer treatment. Although this drug is not specific for cancer cells and also acts on healthy cells, it can cause mucositis, a common collateral effect. Dysbiosis has also been described in 5-fluorouracil-induced mucositis and is likely to contribute to the overall development of mucositis. In light of this theory, the use of probiotics could be a helpful strategy to alleviate mucositis. So the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…However, not all the research studies demonstrated beneficial effects of probiotics on chemotherapy‐induced mucositis. Maioli et al . showed that Saccharomyces boulardii was not able to ameliorate the effects of mucositis induced by 5‐FU.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all the research studies demonstrated beneficial effects of probiotics on chemotherapy‐induced mucositis. Maioli et al . showed that Saccharomyces boulardii was not able to ameliorate the effects of mucositis induced by 5‐FU.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal permeability was evaluated according to Maioli et al (2014). All mice received 0.1 ml diethylenetriaminepentaacetic acid (Nuclefar) solution labelled with 18.5 MBq of 99m-technetium by gavage.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy-induced mucositis can limit the dose of chemotherapy and increase the risk of infection or hospitalization. Consequently, mucositis during chemotherapy could increase clinical and economic burdens (4). 5-Fluorouracil (5-FU) is a frequently prescribed anticancer agent; however, it commonly causes chemotherapy-related mucositis.…”
Section: Introductionmentioning
confidence: 99%